Enhancement of electrical conductivity in plasticized chitosan based membranes - Mattos, R.I.; Raphael, E.; Majid, Siti Rohana; Arof, Abdul Kariem; Pawlicka, A. (Taylor & Francis, 2012)
Plasticized natural macromolecules-based polymer electrolyte samples were prepared and characterized. The plasticization of chitosonium acetate with glycerol increased the ionic conductivity value from 3.0 x 10(-7) S/cm to 1.1 x 10(-5) S/cm. The conductivity temperature relationship of the samples exhibits either VTF or Arrhenius type depending on the glycerol concentration in the sample. The dielectric studies evidencing the relaxation process in the plasticized sample at low frequency region are due to the electric polarization effect. Moreover, the samples were transparent in the Vis region, showed thermal stability up to 160 degrees C and good surface uniformity.